THE ROLE OF PRISON OFFICERS IN LAW ENFORCEMENT AND THE ENFORCEMENT OF THE MINISTRY OF LAW AND HUMAN RIGHTS REGULATION NUMBER 6 OF 2013, AND ITS OBSTACLES IN COMBATING DRUG TRAFFICKING IN CLASS IA CORRECTIONAL INSTITUTIONS IN SEMARANG - Satrio Rilo Pambudi; Dyah Listyarini; Adi Suliantoro (Jurnal Ilmiah Advokasi, 2024)
Drug abuse within prisons is not only considered a serious disciplinary violation but is also regulated by Article 9 Paragraph (4) of the Ministerial Regulation Number 6 of 2013 regarding the Code of Conduct for Correctional Institutions and State Detention Houses. Prison officers (Sipir) are expected to carry out their duties effectively, particularly in maintaining discipline among inmates and preventing drug smuggling. The research problem formulation involves three main aspects: the role of prison officers in implementing the regulations of the Ministry of Law and Human Rights Number 6 of 2013 in Class IA Semarang Prison, the sanctions imposed for drug smuggling violations in the Correctional Institution, and the obstacles faced by prison officers in law enforcement related to drug smuggling in Class IA Semarang Prison. A Juridical Sociological research method is employed to gain empirical legal knowledge through direct field research. The research results indicate that the role of prison officers, in accordance with the Ministry of Law and Human Rights Regulation Number 29 of 2017, has been carried out effectively. Sanctions for drug smuggling violations within the correctional institution include visitation restrictions, inability to apply for remission, parole, and conditional release, as well as assimilation for 9 months with placement in a strapped cell. However, the obstacles faced by prison officers are not only internal, involving fellow staff or correctional officers, but also stem from visits that do not adhere to regulations. This highlights the necessity for the involvement of internal institutional collaboration and cooperation with external parties to achieve full effectiveness in combating drug smuggling in the prison. Keywords: Correctional Institution; Drugs; Prison Officer